Accounting Information of Earnings Management That Be Used To Predict an Investment Decision in The Banking Sector - Himmah, Inda Faiqotul; Pujiono (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
Accounting information is needed by earnings management to prepare company activity plans. Earnings management accounting information is very useful at the stage of analyzing the consequences of each alternative. Actions used in predicting investment decisions are based on accounting information. The research objective is to analyze the effectiveness of earnings management accounting information used to predict investment decisions in the banking sector. The data used is secondary data. The data analysis method used is descriptive statistical methods. The results of this research show that although there are differences in characteristics between earnings management and predicting investment decisions, this does not make a difference between earnings management and predicting investment decisions. The research results show that the higher the company practices earnings management, the higher the value of the company and banking sector companies in stock investment decisions, especially fundamental analysis information. Based on accounting information, management can make good stock investment decisions by analyzing fundamentals so that losses can be avoided.